Ultra-high performance concrete as well as preparation method and application thereof

By optimizing the ratio and process, combined with the use of nanomodifiers, the problems of high production costs and complex processes of traditional UHPC are solved, and ultra-high performance concrete with high strength, durability and sustainability are achieved, which is suitable for a variety of engineering applications.

CN119822726AInactive Publication Date: 2025-04-15CHANGCHUN URBAN CONSTR & MAINTENANCE GRP CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510011644.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-04
Publication Date
2025-04-15
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional ultra-high performance concrete (UHPC) has problems in high production costs, complex processes, hydration heat and volume shrinkage, which limits its wide application in ordinary engineering.

Method used

Through the optimization of the ratio design and preparation process, a new ultra-high performance concrete is prepared using ordinary silicate cement (P.O 42.5) and mineral blends, combined with nanomodifier preparation methods, including hydrothermal synthesis, dialysis and ultrasonic mixing.

Benefits of technology

It achieves excellent mechanical properties, excellent durability, reduced structural self-weight and sustainability, and is suitable for bridges, tunnels, high-rise buildings and other fields, reducing production costs and construction difficulties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119822726A_ABST
    Figure CN119822726A_ABST
Patent Text Reader

Abstract

The invention discloses ultra-high performance concrete as well as a preparation method and application thereof, and relates to the technical field of polymer modified materials. The invention relates to a cement-kaolin-based nano-modifier, which comprises cement, kaolin, a nano-modifier and water, wherein P.O 42.5 type ordinary Portland cement and high-purity kaolin are particularly used in the cement-kaolin-based nano-modifier. The nano modifier is prepared by mixing magnesium sulfate, tetraethyl silicate, (3-aminopropyl) trimethoxysilane and ultrapure water and carrying out a hydrothermal synthesis reaction. The preparation method of the concrete comprises the following steps: mixing the components in proportion, uniformly stirring, injecting into a mold, and carrying out wet curing at specific humidity and temperature. The ultra-high performance concrete shows excellent compressive strength and tensile strength, is excellent in durability, can resist high temperature, freeze-thaw cycle and corrosion environments, and is especially suitable for engineering application requiring high strength and durability, such as port concrete slope walls.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polymer modified materials, in particular to ultra-high performance concrete and a preparation method and application thereof. Background Art

[0002] As an important building material, concrete has been widely used in the fields of construction and civil engineering due to its easy availability of raw materials, low cost, high strength and good durability. However, traditional concrete also has some significant defects, such as low tensile strength, heavy weight and insufficient durability, which limits its application in some high-demand projects. In addition, with the development of modern construction technology and the increasing requirements for sustainability, traditional concrete has been unable to meet the complex engineering environment and high performance requirements.

[0003] In order to solve these problems, high-performance concrete (HPC) and ultra-high performance concrete (UHPC) came into being. As a new type of cement-based composite material, UHPC has become an important breakthrough in the field of building materials with its ultra-high strength, excellent toughness and durability. At present, UHPC has been widely studied and applied worldwide. For example: in bridge engineering, it is used to manufacture the main beams and bridge decks of long-span bridges to improve the structural bearing capacity and extend the service life. In the construction field, it is used to make lightweight stairs, high-rise building support columns, etc., to improve seismic resistance and design flexibility. In transportation infrastructure, it is used for tunnel linings, anti-collision guardrails, etc. to enhance durability and safety. Although UHPC performs well in many aspects, its promotion still faces certain challenges, including high production costs, complex preparation processes, and large volume shrinkage. Therefore, continuous optimization of mix design, simplification of production processes, and cost reduction are important directions for future research. At the same time, there are few studies on ultra-high performance concrete using traditional low-cost PO 42.5 cement. Most UHPC research focuses on the application of high-grade cement (such as CP-V-ARI), while research on the use of ordinary Portland cement (PO 42.5) is relatively limited. However, PO 42.5 cement has the following potentials: Cost advantage: Compared with special cement, it is cheaper and more widely available, which helps to reduce the overall cost of UHPC. Sustainability: Combined with mineral admixtures, it can reduce cement usage and reduce carbon emissions.

[0004] In short, although UHPC faces certain obstacles to promotion, through technological innovation and material optimization, its application prospects in bridges, tunnels, high-rise buildings and other fields are still broad. Summary of the invention

[0005] The present invention aims to provide an ultra-high performance concrete (UHPC) and its preparation method and application. Although it has shown significant advantages in the field of building materials, there are still some problems that need to be overcome. Existing problems: High production cost: The raw materials of UHPC, such as silica fume, quartz sand, steel fiber, etc., are expensive, making the material cost of UHPC much higher than that of ordinary concrete, about 10 times more. This high cost limits the wide application of UHPC in ordinary engineering. Complex production process: The preparation of UHPC requires precise proportions and complex process flows, including high-temperature steam curing, etc. These processes are not only energy-intensive, but also difficult to implement in on-site construction. In addition, the high viscosity and slump loss of UHPC slurry also increase the difficulty of construction. Hydration heat and volume shrinkage problems: Due to the high amount of cement in UHPC, the hydration heat increases, which in turn causes volume shrinkage. This phenomenon may cause structural cracking and affect long-term durability. Fluidity problem: Due to the addition of a large amount of fibers and ultrafine particles, UHPC has poor fluidity, which is not conducive to casting and molding, and the fibers are easy to agglomerate, affecting the uniformity and mechanical properties of concrete.

[0006] The present invention has the following advantages: Excellent mechanical properties: UHPC has extremely high compressive strength and tensile strength, which enables it to withstand load conditions in harsh environments, such as bridges, tunnels and port projects. This performance advantage makes UHP C have significant application value in projects that require high strength and durability. Excellent durability: UHPC exhibits extremely low porosity and excellent crack resistance, and can effectively resist environmental factors such as chloride ion erosion and freeze-thaw cycles, thereby increasing the service life of the structure. This makes UHPC particularly suitable for use in marine engineering and other harsh environments. Reduce the dead weight of the structure: Due to its high strength characteristics, UHPC can reduce the dead weight of the structure, which not only helps save materials, but also reduces construction costs and transportation costs. This is especially important for architectural designs that require lightweight structures. Sustainability: By using ordinary Portland cement (P.O42.5) in combination with mineral admixtures, the present invention reduces carbon emissions while reducing material costs, which helps to achieve sustainable development of building materials. Potential for wide application: With its excellent performance, UHPC has broad application prospects in the fields of bridges, subways, dams, etc., which can not only improve structural safety, but also extend service life and reduce maintenance requirements. In summary, the present invention shows significant advantages in mechanical properties, durability, economic benefits, etc. by optimizing the ratio design and preparation process. However, in order to achieve wider application, it is necessary to further solve the problems of high production cost and complex process to promote the popularization of UHPC in actual engineering.

[0007] To achieve the above object, the present invention provides the following technical solutions:

[0008] An ultra-high performance concrete, comprising the following components:

[0009]

[0010] Mix and dissolve magnesium sulfate, tetraethyl silicate, (3-aminopropyl)trimethoxysilane and ultrapure water in a mass volume ratio of (20 mg-30 mg): (2 mL-6 mL): (1 mL-3 mL): (15 mL-25 mL) to obtain a mixed solution; transfer the mixed solution to a hydrothermal synthesis reactor with a polytetrafluoroethylene liner for reaction, heat the oven to 180°C-240°C for reaction, control the reaction time to 8h-12h, obtain a reaction solution, and cool the reaction solution to room temperature after reaction; centrifuge the reaction solution and collect the supernatant.

[0011] Next, the collected supernatant was mixed with ethylene glycol, triethanolamine and sodium citrate, wherein the mass volume ratio of the supernatant, ethylene glycol, triethanolamine and sodium citrate was (10 mL-20 mL): (4 g-10 g): (5 mL-10 mL): (0.1 g-0.8 g), and the mixture was mixed at room temperature on a shaker at 400 rpm for 6 h-12 h until the solution turned light yellow, and the solution was dialyzed using a 5000 Da dialysis membrane, the retentate was recovered, and dispersed in 100 mL of polyvinyl alcohol solution to obtain a viscous complex;

[0012] Finally, the viscous complex obtained above is ultrasonically mixed with propylene glycol, calcium oxalate and ultrapure water, wherein the mass volume ratio of the viscous complex, propylene glycol, calcium oxalate and ultrapure water is 6g:14mL:0.8g:60mL. The black precipitate is collected and dried in vacuum.

[0013] Preferably, the ultra-high performance concrete comprises the following components:

[0014]

[0015] Preferably, the ultra-high performance concrete comprises the following components:

[0016]

[0017]

[0018] Preferably, the cement is of PO 42.5 type, and its chemical composition is as follows:

[0019] In terms of weight percentage, calcium oxide: 62%-67%, silicon dioxide: 20%-24%, aluminum oxide: 4%-7%, and iron oxide: 2%-6%.

[0020] Preferably, the composition of kaolin is Al2Si2O5(OH)4, the purity is above 93%, and the density is 2.54-2.60g / cm 3 The average particle size is 0.5 μm and its specific surface area is 24 m 2 / g.

[0021] The method for preparing the ultra-high performance concrete as described above comprises the following steps:

[0022] Weigh cement, kaolin, nano-modifier and water according to weight to ensure that the quality of each component meets the requirements; kaolin needs to be dried to ensure that the moisture content is less than 0.5%; then, first mix water with the nano-modifier and stir evenly to form a modified homogeneous solution; then, add kaolin and one-third of the mass of cement into the mixer and stir for 1-2min. This step requires a high speed of stirring, set to 80rpm; gradually add the remaining cement and modified homogeneous solution, continue stirring for 3-5min, this step requires a high speed of stirring, set to 80rpm, to obtain slurry; inject the evenly stirred slurry into a pre-prepared mold and vibrate it slightly to eliminate bubbles and ensure compactness; after initial setting, place the mold in an environment with a humidity of more than 95% and a temperature of 20℃-25℃ for wet curing for 24h; after demolding, transfer the concrete specimen to a constant temperature and humidity environment and continue to cure to the design age.

[0023] The application of ultra-high performance concrete in the preparation of port concrete slope protection wall as described above.

[0024] Beneficial Effects

[0025] Ultra-high performance concrete (UHPC) is particularly suitable for port revetment walls that are subject to complex stress conditions in the marine environment due to its excellent compressive and tensile strength. The compressive strength of UHPC can exceed 150MPa, and the tensile strength is also significantly improved, which enables it to effectively resist the structural stress caused by wave impact and tidal changes. This high-strength characteristic not only improves the bearing capacity of the revetment wall, but also extends its service life. In the port environment, concrete structures are often exposed to salt water, moisture and corrosive substances. UHPC effectively prevents the penetration of moisture and chloride ions through its low porosity and excellent crack resistance, thereby significantly improving the durability of the structure. Corrosion resistance tests show that UHPC shows extremely high resistance in saturated NaCl solution, and there is no obvious corrosion mark on its surface compared with traditional concrete. This durability makes UHPC an ideal material for port revetment walls, reducing the frequency of maintenance and repair. UHPC shows excellent stability under high temperature and freeze-thaw cycle conditions. The experimental results show that the UHPC structure is intact and crack-free after high-temperature treatment at 200°C, and remains intact after repeated freeze-thaw cycles. This is particularly important for port revetment walls that need to face extreme temperature changes, as it ensures the long-term stability of the structure in harsh environments. Although the initial material cost of UHPC is relatively high, its excellent durability and low maintenance requirements make the overall economic benefits significant. In addition, the present invention uses ordinary Portland cement (PO 42.5) combined with mineral admixtures, which not only reduces material costs, but also reduces carbon emissions, meeting the requirements of modern buildings for sustainable development. This material selection not only reduces production costs, but also improves the feasibility of UHPC applications in large-scale projects. UHPC is highly flexible in design and can meet the needs of revetment walls of different shapes and sizes. This flexibility enables engineers to customize designs according to specific project requirements, thereby optimizing structural performance and reducing construction difficulty.

[0026] In summary, the ultra-high performance concrete of the present invention provides an ideal solution for port concrete slope protection walls through its excellent mechanical properties, durability, high temperature and freeze-thaw stability, as well as its economic and sustainable advantages. It not only meets the strict requirements of marine engineering on material performance, but also provides a reference example for similar projects in the future, which helps to promote the development and innovation in the field of building materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 It is the demoulding diagram of the concrete specimen (taking Example 3 as an example).

[0028] Figure 2 It is the maintenance diagram of the concrete specimen (taking Example 3 as an example).

[0029] Figure 3These are high temperature test result diagrams of concrete specimens prepared in Example 3 and Comparative Example 3; the upper diagram is a high temperature test result diagram of Example 3, and the lower diagram is a high temperature test result diagram of Comparative Example 3.

[0030] Figure 4 The freeze-thaw cycle test results of the concrete specimens prepared in Example 3 and Comparative Example 3 are shown in the figure; the upper figure is the freeze-thaw cycle test results of Example 3, and the lower figure is the freeze-thaw cycle test results of Comparative Example 3.

[0031] Figure 5 These are the corrosion resistance test result diagrams of the concrete specimens prepared in Example 3 and Comparative Example 3; the left diagram is the corrosion resistance result diagram of Example 3, and the right diagram is the corrosion resistance result diagram of Comparative Example 3. DETAILED DESCRIPTION

[0032] The reagents involved in the present invention are all analytically pure.

[0033] Example 1

[0034] Ultra-high performance concrete, including the following components:

[0035]

[0036] The preparation method of the nano modifier is as follows:

[0037] Mix and dissolve magnesium sulfate, tetraethyl silicate, (3-aminopropyl)trimethoxysilane and ultrapure water in a mass volume ratio of 20 mg: 6 mL: 1 mL: 25 mL to obtain a mixed solution; transfer the mixed solution to a hydrothermal synthesis reactor with a polytetrafluoroethylene liner for reaction, heat the oven to 180° C. for reaction, control the reaction time to 12 h, obtain a reaction solution, and cool the reaction solution to room temperature after completion; centrifuge the reaction solution and collect the supernatant;

[0038] Next, the collected supernatant was mixed with ethylene glycol, triethanolamine and sodium citrate, wherein the mass volume ratio of the supernatant, ethylene glycol, triethanolamine and sodium citrate was 10 mL: 10 g: 5 mL: 0.8 g, and the mixture was mixed at 400 rpm on a shaker at room temperature for 6 h until the solution turned light yellow. The solution was dialyzed using a 5000 Da dialysis membrane, and the retentate was recovered and dispersed in 100 mL of polyvinyl alcohol solution to obtain a viscous complex.

[0039] Finally, the viscous complex obtained above is ultrasonically mixed with propylene glycol, calcium oxalate and ultrapure water, wherein the mass volume ratio of the viscous complex, propylene glycol, calcium oxalate and ultrapure water is 6g:14mL:0.8g:60mL. The black precipitate is collected and dried in vacuum.

[0040] The cement is PO 42.5 type, and its chemical composition is as follows:

[0041] In terms of weight percentage, calcium oxide: 62%, silicon dioxide: 24%, aluminum oxide: 4%, and iron oxide: 6%.

[0042] The composition of kaolin is Al2Si2O5(OH)4, its purity is 96%, and its density is 2.54g / cm 3 The average particle size is 0.5 μm and its specific surface area is 24 m 2 / g.

[0043] The method for preparing the ultra-high performance concrete as described above comprises the following steps:

[0044] Weigh cement, kaolin, nano-modifier and water according to weight to ensure that the quality of each component meets the requirements; kaolin needs to be dried to ensure that the moisture content is 0.3%; then, first mix water and nano-modifier, stir evenly to form a modified homogeneous solution; then, add kaolin and one-third of the mass of cement into the mixer and stir for 1 minute; gradually add the remaining cement and modified homogeneous solution, continue stirring for 5 minutes to obtain slurry; inject the evenly stirred slurry into a pre-prepared mold, vibrate slightly to eliminate bubbles and ensure compactness; after initial setting, place the mold in an environment with a humidity of 96% and a temperature of 20°C for wet curing for 24 hours; after demolding, transfer the concrete specimen to a constant temperature and humidity environment and continue curing to the design age.

[0045] Example 2

[0046] Ultra-high performance concrete, including the following components:

[0047]

[0048] The preparation method of the nano modifier is as follows:

[0049] Mix and dissolve magnesium sulfate, tetraethyl silicate, (3-aminopropyl)trimethoxysilane and ultrapure water in a mass volume ratio of 30 mg: 2 mL: 3 mL: 15 mL to obtain a mixed solution; transfer the mixed solution to a hydrothermal synthesis reactor with a polytetrafluoroethylene liner for reaction, heat the oven to 240° C. for reaction, control the reaction time to 8 h, obtain a reaction solution, and cool the reaction solution to room temperature after completion; centrifuge the reaction solution and collect the supernatant;

[0050] Next, the collected supernatant was mixed with ethylene glycol, triethanolamine and sodium citrate, wherein the mass volume ratio of the supernatant, ethylene glycol, triethanolamine and sodium citrate was 20 mL: 4 g: 10 mL: 0.1 g, and the mixture was mixed at 400 rpm on a shaker at room temperature for 12 h until the solution turned light yellow. The solution was dialyzed using a 5000 Da dialysis membrane, and the retentate was recovered and dispersed in 100 mL of polyvinyl alcohol solution to obtain a viscous complex.

[0051] Finally, the viscous complex obtained above is ultrasonically mixed with propylene glycol, calcium oxalate and ultrapure water, wherein the mass volume ratio of the viscous complex, propylene glycol, calcium oxalate and ultrapure water is 6g:14mL:0.8g:60mL. The black precipitate is collected and dried in vacuum.

[0052] The cement is PO 42.5 type, and its chemical composition is as follows:

[0053] In terms of weight percentage, calcium oxide: 67%, silicon dioxide: 20%, aluminum oxide: 7%, and iron oxide: 2%.

[0054] The composition of kaolin is Al2Si2O5(OH)4, its purity is 96%, and its density is 2.60g / cm 3 The average particle size is 0.5 μm and its specific surface area is 24 m 2 / g.

[0055] The method for preparing the ultra-high performance concrete as described above comprises the following steps:

[0056] Weigh cement, kaolin, nano-modifier and water according to weight to ensure that the quality of each component meets the requirements; kaolin needs to be dried to ensure that the moisture content is 0.2%; then, first mix water and nano-modifier, stir evenly to form a modified homogeneous solution; then, add kaolin and one-third of the mass of cement into the mixer and stir for 2 minutes; gradually add the remaining cement and modified homogeneous solution, continue stirring for 3 minutes to obtain slurry; inject the evenly stirred slurry into a pre-prepared mold, vibrate slightly to eliminate bubbles and ensure compactness; after initial setting, place the mold in an environment with a humidity of 96% and a temperature of 25°C for wet curing for 24 hours; after demolding, transfer the concrete specimen to a constant temperature and humidity environment and continue curing to the design age.

[0057] Example 3

[0058] Ultra-high performance concrete, including the following components:

[0059]

[0060] The preparation method of the nano modifier is as follows:

[0061] Mix and dissolve magnesium sulfate, tetraethyl silicate, (3-aminopropyl)trimethoxysilane and ultrapure water in a mass volume ratio of 20 mg: 2 mL: 1 mL: 15 mL to obtain a mixed solution; transfer the mixed solution to a hydrothermal synthesis reactor with a polytetrafluoroethylene liner for reaction, heat the oven to 180° C. for reaction, control the reaction time to 8 h, obtain a reaction solution, and cool the reaction solution to room temperature after completion; centrifuge the reaction solution and collect the supernatant;

[0062] Next, the collected supernatant was mixed with ethylene glycol, triethanolamine and sodium citrate, wherein the mass volume ratio of the supernatant, ethylene glycol, triethanolamine and sodium citrate was 10 mL: 4 g: 5 mL: 0.1 g, and the mixture was mixed at 400 rpm on a shaker at room temperature for 6 h until the solution turned light yellow. The solution was dialyzed using a 5000 Da dialysis membrane, and the retentate was recovered and dispersed in 100 mL of polyvinyl alcohol solution to obtain a viscous complex.

[0063] Finally, the viscous complex obtained above is ultrasonically mixed with propylene glycol, calcium oxalate and ultrapure water, wherein the mass volume ratio of the viscous complex, propylene glycol, calcium oxalate and ultrapure water is 6g:14mL:0.8g:60mL. The black precipitate is collected and dried in vacuum.

[0064] The cement is PO 42.5 type, and its chemical composition is as follows:

[0065] In terms of weight percentage, calcium oxide: 62%, silicon dioxide: 20%, aluminum oxide: 4%, and iron oxide: 2%.

[0066] The composition of kaolin is Al2Si2O5(OH)4, its purity is 97%, and its density is 2.54g / cm 3 The average particle size is 0.5 μm and its specific surface area is 24 m 2 / g.

[0067] The method for preparing the ultra-high performance concrete as described above comprises the following steps:

[0068] Weigh cement, kaolin, nano-modifier and water according to weight to ensure that the quality of each component meets the requirements; kaolin needs to be dried to ensure that the moisture content is 0.4%; then, first mix water and nano-modifier, stir evenly to form a modified homogeneous solution; then, add kaolin and one-third of the mass of cement into the mixer and stir for 1 minute; gradually add the remaining cement and modified homogeneous solution, continue stirring for 3 minutes to obtain slurry; inject the evenly stirred slurry into a pre-prepared mold, vibrate slightly to eliminate bubbles and ensure compactness; after initial setting, place the mold in an environment with a humidity of 97% and a temperature of 20°C for wet curing for 24 hours; after demolding, transfer the concrete specimen to a constant temperature and humidity environment and continue curing to the design age.

[0069] Example 4

[0070] Ultra-high performance concrete, including the following components:

[0071]

[0072] The preparation method of the nano modifier is as follows:

[0073] Mix and dissolve magnesium sulfate, tetraethyl silicate, (3-aminopropyl)trimethoxysilane and ultrapure water in a mass volume ratio of 30 mg: 6 mL: 3 mL: 25 mL to obtain a mixed solution; transfer the mixed solution to a hydrothermal synthesis reactor with a polytetrafluoroethylene liner for reaction, heat the oven to 240° C. for reaction, control the reaction time to 12 h, obtain a reaction solution, and cool the reaction solution to room temperature after completion; centrifuge the reaction solution and collect the supernatant;

[0074] Next, the collected supernatant was mixed with ethylene glycol, triethanolamine and sodium citrate, wherein the mass volume ratio of the supernatant, ethylene glycol, triethanolamine and sodium citrate was 20 mL:10 g:10 mL:0.8 g, and the mixture was mixed at 400 rpm on a shaker at room temperature for 12 h until the solution turned light yellow, and the solution was dialyzed using a 5000 Da dialysis membrane, and the retentate was recovered and dispersed in 100 mL of polyvinyl alcohol solution to obtain a viscous complex;

[0075] Finally, the viscous complex obtained above is ultrasonically mixed with propylene glycol, calcium oxalate and ultrapure water, wherein the mass volume ratio of the viscous complex, propylene glycol, calcium oxalate and ultrapure water is 6g:14mL:0.8g:60mL. The black precipitate is collected and dried in vacuum.

[0076] The cement is PO 42.5 type, and its chemical composition is as follows:

[0077] In terms of weight percentage, calcium oxide: 67%, silicon dioxide: 24%, aluminum oxide: 7%, and iron oxide: 6%.

[0078] The composition of kaolin is Al2Si2O5(OH)4, its purity is 98%, and its density is 2.60g / cm 3 The average particle size is 0.5 μm and its specific surface area is 24 m 2 / g.

[0079] The method for preparing the ultra-high performance concrete as described above comprises the following steps:

[0080] Weigh cement, kaolin, nano-modifier and water according to weight to ensure that the quality of each component meets the requirements; kaolin needs to be dried to ensure that the moisture content is 0.3%; then, first mix water and nano-modifier, stir evenly to form a modified homogeneous solution; then, add kaolin and one-third of the mass of cement into the mixer and stir for 2 minutes; gradually add the remaining cement and modified homogeneous solution, continue stirring for 5 minutes to obtain slurry; inject the evenly stirred slurry into a pre-prepared mold, vibrate slightly to eliminate bubbles and ensure compactness; after initial setting, place the mold in an environment with a humidity of 98% and a temperature of 25°C for wet curing for 24 hours; after demolding, transfer the concrete specimen to a constant temperature and humidity environment and continue curing to the design age.

[0081] Example 5

[0082] Ultra-high performance concrete, including the following components:

[0083]

[0084] The preparation method of the nano modifier is as follows:

[0085] Mix and dissolve magnesium sulfate, tetraethyl silicate, (3-aminopropyl)trimethoxysilane and ultrapure water in a mass volume ratio of 25 mg: 4 mL: 2 mL: 20 mL to obtain a mixed solution; transfer the mixed solution to a hydrothermal synthesis reactor with a polytetrafluoroethylene liner for reaction, heat the oven to 210° C. for reaction, control the reaction time to 10 h, obtain a reaction solution, and cool the reaction solution to room temperature after completion; centrifuge the reaction solution and collect the supernatant;

[0086] Next, the collected supernatant was mixed with ethylene glycol, triethanolamine and sodium citrate, wherein the mass volume ratio of the supernatant, ethylene glycol, triethanolamine and sodium citrate was 15 mL: 8 g: 8 mL: 0.5 g, and the mixture was mixed at 400 rpm on a shaker at room temperature for 9 h until the solution turned light yellow. The solution was dialyzed using a 5000 Da dialysis membrane, and the retentate was recovered and dispersed in 100 mL of polyvinyl alcohol solution to obtain a viscous complex.

[0087] Finally, the viscous complex obtained above is ultrasonically mixed with propylene glycol, calcium oxalate and ultrapure water, wherein the mass volume ratio of the viscous complex, propylene glycol, calcium oxalate and ultrapure water is 6g:14mL:0.8g:60mL. The black precipitate is collected and dried in vacuum.

[0088] The cement is PO 42.5 type, and its chemical composition is as follows:

[0089] In terms of weight percentage, calcium oxide: 65%, silicon dioxide: 22%, aluminum oxide: 6%, and iron oxide: 4%.

[0090] The composition of kaolin is Al2Si2O5(OH)4, its purity is 98%, and its density is 2.58g / cm 3 The average particle size is 0.5 μm and its specific surface area is 24 m 2 / g.

[0091] The method for preparing the ultra-high performance concrete as described above comprises the following steps:

[0092] Weigh cement, kaolin, nano-modifier and water according to weight to ensure that the quality of each component meets the requirements; kaolin needs to be dried to ensure that the moisture content is 0.4%; then, first mix water and nano-modifier, stir evenly to form a modified homogeneous solution; then, add kaolin and one-third of the mass of cement into the mixer and stir for 1.5 minutes; gradually add the remaining cement and modified homogeneous solution, continue stirring for 4 minutes to obtain slurry; inject the evenly stirred slurry into a pre-prepared mold, vibrate slightly to eliminate bubbles and ensure compactness; after initial setting, place the mold in an environment with a humidity of 98% and a temperature of 23°C for wet curing for 24 hours; after demolding, transfer the concrete specimen to a constant temperature and humidity environment and continue curing to the design age.

[0093] Comparative Example 1

[0094] Ultra-high performance concrete, including the following components:

[0095]

[0096] The preparation method of the nano modifier is as follows:

[0097] Magnesium sulfate, (3-aminopropyl)trimethoxysilane and ultrapure water are mixed and dissolved in a mass volume ratio of 25 mg: 2 mL: 20 mL to obtain a mixed solution; the mixed solution is transferred to a hydrothermal synthesis reactor with a polytetrafluoroethylene liner for reaction, the temperature is raised to 210° C. in an oven for reaction, the reaction time is controlled to 10 h, and a reaction solution is obtained, and the reaction solution is cooled to room temperature after the reaction is completed; the reaction solution is centrifuged and the supernatant is collected;

[0098] Next, the collected supernatant was mixed with ethylene glycol, triethanolamine and sodium citrate, wherein the mass volume ratio of the supernatant, ethylene glycol, triethanolamine and sodium citrate was 15 mL: 8 g: 8 mL: 0.5 g, and the mixture was mixed at 400 rpm on a shaker at room temperature for 9 h until the solution turned light yellow. The solution was dialyzed using a 5000 Da dialysis membrane, and the retentate was recovered and dispersed in 100 mL of polyvinyl alcohol solution to obtain a viscous complex.

[0099] Finally, the viscous complex obtained above is ultrasonically mixed with propylene glycol, calcium oxalate and ultrapure water, wherein the mass volume ratio of the viscous complex, propylene glycol, calcium oxalate and ultrapure water is 6g:14mL:0.8g:60mL. The black precipitate is collected and dried in vacuum.

[0100] The cement is PO 42.5 type, and its chemical composition is as follows:

[0101] In terms of weight percentage, calcium oxide: 65%, silicon dioxide: 22%, aluminum oxide: 6%, and iron oxide: 4%.

[0102] The composition of kaolin is Al2Si2O5(OH)4, its purity is 98%, and its density is 2.58g / cm 3 The average particle size is 0.5 μm and its specific surface area is 24 m 2 / g.

[0103] The method for preparing the ultra-high performance concrete as described above comprises the following steps:

[0104] Weigh cement, kaolin, nano-modifier and water according to weight to ensure that the quality of each component meets the requirements; kaolin needs to be dried to ensure that the moisture content is 0.4%; then, first mix water and nano-modifier, stir evenly to form a modified homogeneous solution; then, add kaolin and one-third of the mass of cement into the mixer and stir for 1.5 minutes; gradually add the remaining cement and modified homogeneous solution, continue stirring for 4 minutes to obtain slurry; inject the evenly stirred slurry into a pre-prepared mold, vibrate slightly to eliminate bubbles and ensure compactness; after initial setting, place the mold in an environment with a humidity of 98% and a temperature of 23°C for wet curing for 24 hours; after demolding, transfer the concrete specimen to a constant temperature and humidity environment and continue curing to the design age.

[0105] Comparative Example 2

[0106] Ultra-high performance concrete, including the following components:

[0107]

[0108] The preparation method of the nano modifier is as follows:

[0109] Mix and dissolve magnesium sulfate, tetraethyl silicate and ultrapure water in a mass volume ratio of 25 mg: 4 mL: 20 mL to obtain a mixed solution; transfer the mixed solution to a hydrothermal synthesis reactor with a polytetrafluoroethylene liner for reaction, heat the oven to 210° C. for reaction, control the reaction time to 10 h, obtain a reaction solution, and cool the reaction solution to room temperature after completion; centrifuge the reaction solution and collect the supernatant;

[0110] Next, the collected supernatant was mixed with ethylene glycol, triethanolamine and sodium citrate, wherein the mass volume ratio of the supernatant, ethylene glycol, triethanolamine and sodium citrate was 15 mL: 8 g: 8 mL: 0.5 g, and the mixture was mixed at 400 rpm on a shaker at room temperature for 9 h until the solution turned light yellow. The solution was dialyzed using a 5000 Da dialysis membrane, and the retentate was recovered and dispersed in 100 mL of polyvinyl alcohol solution to obtain a viscous complex.

[0111] Finally, the viscous complex obtained above is ultrasonically mixed with propylene glycol, calcium oxalate and ultrapure water, wherein the mass volume ratio of the viscous complex, propylene glycol, calcium oxalate and ultrapure water is 6g:14mL:0.8g:60mL. The black precipitate is collected and dried in vacuum.

[0112] The cement is PO 42.5 type, and its chemical composition is as follows:

[0113] In terms of weight percentage, calcium oxide: 65%, silicon dioxide: 22%, aluminum oxide: 6%, and iron oxide: 4%.

[0114] The composition of kaolin is Al2Si2O5(OH)4, its purity is 98%, and its density is 2.58g / cm 3 The average particle size is 0.5 μm and its specific surface area is 24 m 2 / g.

[0115] The method for preparing the ultra-high performance concrete as described above comprises the following steps:

[0116] Weigh cement, kaolin, nano-modifier and water according to weight to ensure that the quality of each component meets the requirements; kaolin needs to be dried to ensure that the moisture content is 0.4%; then, first mix water and nano-modifier, stir evenly to form a modified homogeneous solution; then, add kaolin and one-third of the mass of cement into the mixer and stir for 1.5 minutes; gradually add the remaining cement and modified homogeneous solution, continue stirring for 4 minutes to obtain slurry; inject the evenly stirred slurry into a pre-prepared mold, vibrate slightly to eliminate bubbles and ensure compactness; after initial setting, place the mold in an environment with a humidity of 98% and a temperature of 23°C for wet curing for 24 hours; after demolding, transfer the concrete specimen to a constant temperature and humidity environment and continue curing to the design age.

[0117] Comparative Example 3

[0118] Ultra-high performance concrete, including the following components:

[0119] Cement 140kg,

[0120] Kaolin 14kg,

[0121] Water 42kg.

[0122] The cement is PO 42.5 type, and its chemical composition is as follows:

[0123] In terms of weight percentage, calcium oxide: 65%, silicon dioxide: 22%, aluminum oxide: 6%, and iron oxide: 4%.

[0124] The composition of kaolin is Al2Si2O5(OH)4, its purity is 98%, and its density is 2.58g / cm 3 The average particle size is 0.5 μm and its specific surface area is 24 m 2 / g.

[0125] The method for preparing the ultra-high performance concrete as described above comprises the following steps:

[0126] Weigh cement, kaolin and water according to weight to ensure that the quality of each component meets the requirements; kaolin needs to be dried to ensure that the moisture content is 0.4%; then, first mix water with the nano modifier and stir evenly to form a modified homogeneous solution; then, add kaolin and one-third of the mass of cement into the mixer and stir for 1.5 minutes; gradually add the remaining cement and modified homogeneous solution, continue stirring for 4 minutes to obtain slurry; inject the evenly stirred slurry into a pre-prepared mold, vibrate slightly to eliminate bubbles and ensure compactness; after initial setting, place the mold in an environment with a humidity of 98% and a temperature of 23°C for wet curing for 24 hours; after demolding, transfer the concrete specimen to a constant temperature and humidity environment and continue curing to the design age.

[0127] The testing process is as follows:

[0128] like Figure 1 and Figure 2 As shown, the concrete specimens prepared after demoulding of Examples 1-5 and Comparative Examples 1-3 were further cured under the following environmental conditions: temperature: maintained at 25°C, humidity: relative humidity maintained at 96%, cycle: 28 days. The dimensions of the concrete specimens are as follows: length 2200 mm, width 150 mm and height 300 mm. Then, the following performance tests were performed.

[0129] (1) Basic mechanical properties test

[0130] The compressive strength (ISO 1920-4:2005 "Concrete Test Methods Part 4") and flexural strength (ASTM C78 / C78M-10 Standard Test Method for Flexural Properties of Concrete) of the concrete specimens of Examples 1-5 and Comparative Examples 1-3 were tested, and the results are shown in Table 1 below.

[0131] Table 1 Performance test results

[0132]

[0133]

[0134] (2) High temperature environment test and freeze-thaw cycle test

[0135] High temperature temperature is set to 200 DEG C, and according to the standard heating rate of 5 DEG C / min, the concrete specimens prepared by Example 3 and Comparative Example 3 are heated to 1000 DEG C, and then 2h of dwelling is carried out. Meanwhile, freeze-thaw cycle test, according to ASTM concrete anti-rapid freeze-thaw test method (M.Lee, Y.Huang.Fire-damage or freeze-thaw of strengtheningconcrete using ultra high performance concrete.Adv.Mater.Res., Vol.79-82(2009), pp.2047-2050), at a rate of one cycle per 185min, the sample is subjected to freeze-thaw cycle, and each cycle includes freezing at -18 DEG C for 1.5h, and then thawing at 4 DEG C for 1.5h.

[0136] like Figure 3 As shown, compared with Comparative Example 3, the structure of the concrete sample prepared in Example 3 after high temperature treatment is intact and has no cracks. Figure 4 As shown, compared with Comparative Example 3, the structure of the concrete sample prepared in Example 3 is intact without cracks after repeated freezing and thawing.

[0137] (3) Corrosion resistance test

[0138] According to ASTM standard (ASTM Standard C1202, Standard Test Method for Electrical Indication of Concrete's Ability to Resist Chloride Ion Penetration, ASTM Int., West Conshohocken, PA; 2017.), the operation method is as follows: cut the concrete specimen into samples with a thickness of 50 mm, apply waterproof epoxy resin on the cut surface of the sample to ensure that it is impermeable, place the sample on one side of a saturated NaOH solution and on the other side of a saturated NaCl solution for electrochemical testing; apply a DC voltage of 60 V across the sample for 6 hours.

[0139] like Figure 5As shown, compared with Comparative Example 3, there is no obvious corrosion mark on the surface of the concrete sample prepared in Example 3 after high temperature treatment. Tetraethyl silicate is commonly used to prepare nanomaterials because it is a precursor of silicon dioxide and can form silicon dioxide particles through hydrolysis and condensation reactions. These particles can be used to enhance the mechanical properties and durability of the material. After removing tetraethyl silicate, the composition and structure of the nanomodifier will change. Tetraethyl silicate helps to form a silicon dioxide network in the nanomodifier, which can improve the strength and toughness of the material. Silica particles can provide good corrosion resistance and wear resistance. Removing tetraethyl silicate will weaken these properties and make the material more susceptible to environmental factors such as moisture, acid and alkali. Silica has good chemical stability and can protect the material from chemical erosion. Therefore, removing tetraethyl silicate will significantly affect the function of the nanomodifier, thereby affecting the overall performance of ultra-high performance concrete. This change needs to be compensated by adjusting other ingredients or introducing substitutes to ensure that the final product meets the expected application requirements. The mechanical properties of the nano-modifier of Comparative Example 2 are reduced by removing (3-aminopropyl) trimethoxysilane: after removing (3-aminopropyl) trimethoxysilane, the compressive strength and flexural strength of the concrete will be reduced. According to the test results, compared with the complete formula, the compressive strength of Comparative Example 2 in which the component is removed is 135.20MPa, and the flexural strength is 20.10MPa, while the compressive strength and flexural strength of the complete formula are higher, respectively. This shows that the component plays an important role in enhancing the mechanical properties of the material. The silane coupling agent is generally used to improve the chemical stability and durability of the material. The silane coupling agent can improve the interfacial bonding force between the nanomaterial and the matrix, thereby improving the overall performance of the material.

[0140] Comparative Example 3 removes the nanomodifier, which is intended to address the shortcomings of traditional concrete in terms of strength, durability and sustainability. The following is a detailed analysis of the internal chemical reactions in the nanomodifier preparation method:

[0141] Hydrothermal synthesis reaction:

[0142] Reactants: magnesium sulfate, tetraethyl silicate (TEOS), (3-aminopropyl) trimethoxysilane (APTES), ultrapure water. Reaction process: TEOS is hydrolyzed in water to generate silanol, which then forms silica colloid through condensation reaction. APTES is also hydrolyzed to generate organic modified silanol, which then undergoes co-condensation reaction with the hydrolysis product of TEOS. Magnesium sulfate acts as a template to guide the formation of nanostructures. Synergistic effect: The co-condensation reaction of TEOS and APTES forms organic-inorganic hybrid nanomaterials, which enhance the mechanical properties and interfacial bonding of the material. Magnesium sulfate interacts with silica colloid to form structurally stable nanoparticles.

[0143] Mixing and Dialysis:

[0144] Reactants: supernatant (containing silica colloid), ethylene glycol, triethanolamine, sodium citrate. Reaction process: Ethylene glycol and triethanolamine act as dispersants and stabilizers to prevent nanoparticles from aggregating. Sodium citrate acts as a buffer to adjust the pH value of the solution, promote the dissolution of reactants and the uniformity of the reaction. Synergistic effect: The synergistic effect of ethylene glycol and triethanolamine provides good dispersibility and ensures the uniform distribution of reactants in the solution. Sodium citrate promotes the reaction and the stability of the product by adjusting the pH value.

[0145] Ultrasonic mixing and drying:

[0146] Reactants: viscous complex, propylene glycol, calcium oxalate, ultrapure water.

[0147] Reaction process: Ultrasonic waves are used to fully mix the composite with propylene glycol and calcium oxalate to form a uniform solution. Propylene glycol acts as a solvent and dispersant to help disperse the nanoparticles in the solution. Calcium oxalate acts as a filler to enhance the mechanical properties of the material. Synergistic effect: Propylene glycol promotes the dispersion of nanoparticles and ensures the uniformity of mixing. The interaction between calcium oxalate and the nano-modifier forms a stable composite structure and enhances the mechanical properties of the material.

[0148] Final product analysis:

[0149] The final product is a black precipitate, which is vacuum dried to form a nanomodifier. This nanomodifier contains an organic-inorganic hybrid nanostructure that enhances the following properties of ultra-high performance concrete: Strength and toughness: The silica colloid and organic modifier in the nanomodifier form a dense structural network, which improves the compressive strength and flexural strength of the concrete. Durability: By filling micropores and improving interfacial bonding, the durability and crack resistance of the concrete are enhanced. Chemical stability: The synergistic effect of the organic modifier and filler enhances the chemical stability of the concrete and reduces the impact of chemical erosion.

[0150] In summary, the present invention realizes the preparation of nano-modifiers by precisely controlling the proportions of the components and the reaction conditions. The synergistic effect between the substances is fully reflected in both microstructure and macroscopic performance, so that ultra-high performance concrete has excellent mechanical properties, durability and chemical stability.

[0151] The above describes in detail the preferred implementation of this patent, but this patent is not limited to the above implementation. Various changes can be made within the knowledge scope of ordinary technicians in this field without departing from the purpose of this patent.

Claims

1. An ultra-high performance concrete, characterized in that: The components include: The preparation method of the nano modifier is as follows: Mix and dissolve magnesium sulfate, tetraethyl silicate, (3-aminopropyl)trimethoxysilane and ultrapure water in a mass volume ratio of (20 mg-30 mg): (2 mL-6 mL): (1 mL-3 mL): (15 mL-25 mL) to obtain a mixed solution; transfer the mixed solution to a hydrothermal synthesis reactor with a polytetrafluoroethylene liner for reaction, heat the oven to 180° C.-240° C. for reaction, control the reaction time to 8 h-12 h, obtain a reaction solution, and cool the reaction solution to room temperature after completion; centrifuge the reaction solution and collect the supernatant; Next, the collected supernatant was mixed with ethylene glycol, triethanolamine and sodium citrate, wherein the mass volume ratio of the supernatant, ethylene glycol, triethanolamine and sodium citrate was (10 mL-20 mL): (4 g-10 g): (5 mL-10 mL): (0.1 g-0.8 g), and the mixture was mixed at room temperature on a shaker at 400 rpm for 6 h-12 h until the solution turned light yellow, and the solution was dialyzed using a 5000 Da dialysis membrane, the retentate was recovered, and dispersed in 100 mL of polyvinyl alcohol solution to obtain a viscous complex; Finally, the viscous complex obtained above is ultrasonically mixed with propylene glycol, calcium oxalate and ultrapure water, wherein the mass volume ratio of the viscous complex, propylene glycol, calcium oxalate and ultrapure water is 6g:14mL:0.8g:60mL. The black precipitate is collected and dried in vacuum.

2. The ultra-high performance concrete according to claim 1, characterized in that: The components include:

3. The ultra-high performance concrete according to claim 2, characterized in that: The components include:

4. The ultra-high performance concrete according to claim 1, characterized in that: The cement is PO 42.5 type, and its chemical composition is as follows: In terms of weight percentage, calcium oxide: 62%-67%, silicon dioxide: 20%-24%, aluminum oxide: 4%-7%, and iron oxide: 2%-6%.

5. The ultra-high performance concrete according to claim 1, characterized in that: The composition of kaolin is Al2Si2O5(OH)4, its purity is more than 93%, and its density is 2.54-2.60g / cm 3 The average particle size is 0.5 μm and its specific surface area is 24 m 2 / g.

6. The method for preparing ultra-high performance concrete according to claim 1, characterized in that: The steps include: Weigh cement, kaolin, nano-modifier and water according to weight to ensure that the quality of each component meets the requirements; kaolin needs to be dried to ensure that the moisture content is less than 0.5%; then, first mix water and nano-modifier, stir evenly to form a modified homogeneous solution; then, add kaolin and one-third of the mass of cement into the mixer and stir for 1-2min; gradually add the remaining cement and modified homogeneous solution, continue stirring for 3-5min to obtain slurry; inject the evenly stirred slurry into a pre-prepared mold, vibrate slightly to eliminate bubbles and ensure compactness; after initial setting, place the mold in an environment with a humidity of more than 95% and a temperature of 20℃-25℃ for wet curing for 24h; after demolding, transfer the concrete specimen to a constant temperature and humidity environment and continue curing to the design age.

7. Use of the ultra-high performance concrete as claimed in claim 1 in preparing a port concrete slope protection wall.

Citation Information

Patent Citations

  • Ultrahigh performance sea sand concrete and preparation method thereof

    CN107572969A

  • Preparation method of lithium ion battery negative electrode silicon-carbon composite material

    CN117525321A

  • Process for preparing ultra-high performance concrete by adopting seawater and sea sand

    CN117945713A

  • Aggregate strengthening and toughening modified ultra-high performance concrete and preparation method thereof

    CN118164731A

  • UHPC (Ultra High Performance Concrete) raw material and preparation method thereof

    CN118684455A